RANCANGAN UI/UX APLIKASI PEMBELAJARAN BIMBEL DASAR KOMPUTER MENGUNAKAN METODE USER-CENTERED DESIGN (UCD) - Shoheh Lucky Satia (JEIS: Jurnal Elektro dan Informatika Swadharma, 2025)
The purpose of this study is to design the UI/UX of a basic computer tutoring learning application. The User-Centered Design (UCD) method is employed in designing the UI/UX, encompassing the stages of specifying the context of use, identifying user and organizational requirements, generating design solutions, and evaluating the design through data collection using the literature study method, interviews, and observations. The results of the study are presented in the form of a UI/UX design for a basic computer tutoring learning application, which was tested by users using the System Usability Scale (SUS) with a total score of 915 from 10 respondents. Thus, the average score is 91.5. From the results of this calculation, it can be concluded that the design of the application that has been created is included in the excellent category with a grade of B.Tujuan penelitian ini adalah untuk merancang UI/UX aplikasi pembelajaran bimbel dasar komputer. Metode User-Centered Design (UCD) digunakan dalam merancang UI/UX dengan tahapan specify the context of use , specify the user and organizational requirements, produce design solution, dan evaluate design. Untuk pengumpulan data menggunakan metode studi pustaka, wawancara dan observasi. Hasil penelitian berupa rancangan UI/UX aplikasi pembelajaran bimbel dasar komputer yang telah diuji oleh pengguna menggunakan system usability scale (SUS) dengan total skor sebesar 915 dari 10 responden. Dengan demikian, rata-rata skor adalah 91.5. Dari hasil perhitungan ini, dapat disimpulkan bahwa desain pada aplikasi yang sudah dibuat termasuk kepada kategori yang excellent dengan skala nilai B.